Towards a remote inspection of jet engine blades using time reversal. (12th May 2022) - Farin, Maxime; Prada, Claire; Lhommeau, Tony; El Badaoui, Mohammed; de Rosny, Julien
Abstract: Assessing the state of damage of jet engine blades is a burning issue in aeronautics. However, most nondestructive evaluation procedures require cumbersome installations and removal of the blades from the engines, which is time and money consuming. We present a non-intrusive acoustic monitoring technique that could be applied for fast remote inspection of selected blades inside a jet engine. The technique uses a time reversal mirror in the audible frequency range to selectively excite a targeted blade a few meters away. The resonance frequencies of the blade are measured at the location of the excitation using a laser vibrometer. The technique is first applied on a few individual blades and then inside a jet engine. Selective excitation of a difficult-to-access blade among others inside a cavity is shown. In laboratory, some damage (material removal or slit) is created on a set of initially intact blades, which cause a shift in their resonance frequencies. By evaluating these frequency shifts, we are able to remotely detect millimeter size damage on the blades. Finally, the on-site applicability and the uncertainties of the method are discussed. Highlights: A method is presented to monitor remotely the eigenmodes of jet engine blades. The method is based on time reversal of acousto-elastic waves in air and in the blade. Investigated blades are preferentially excited along their edges. Blades can be selectively excited inside a complex structure or a jet engine. Eigenfrequencies shift of blades permit remote detection of sub-millimeter damage.